Alcohol-perturbed self-assembly of the tobacco mosaic virus coat protein - Abu-Baker, Ismael; Blum, Amy Szuchmacher (Beilstein Journal of Nanotechnology, 2022)
The self-assembly of the tobacco mosaic virus coat protein is significantly altered in alcohol–water mixtures. Alcohol cosolvents stabilize the disk aggregate and prevent the formation of helical rods at low pH. A high alcohol content favours stacked disk assemblies and large rafts, while a low alcohol concentration favours individual disks and short stacks. These effects appear to be caused by the hydrophobicity of the alcohol additive, with isopropyl alcohol having the strongest effect and methanol the weakest. We discuss several effects that may contribute to preventing the protein–protein interactions between disks that are necessary to form helical rods.
Keywords: alcohol; hydrophobic effect; protein assembly; self-assembly; tobacco mosaic virus